Оblicza kultury w słownikach lingwokulturologicznych na przykładzie Kościeja Nieśmiertelnego (Кащея «Кощея» Бессмерт¬ного) - Olechno-Wasiluk, Joanna (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article compares descriptions of a linguistic unit Kashei the Immortal in entries in two linguocultural dictionaries. The choice of the analytical material is based on the fact that in the Russian collective consciousness Kashei the Immortal functions  as one of the most vivid examples of negative characters. The repelling appearance and personality of the character appear in songs, nursery rhymes and puzzles. Moreover, there stories about Kashei are passed from generation to generation. The comparison  of the entry Kashei the Immortal in linguocultural dictionaries aims at determining to what extent common knowledge about the analyzed linguistic unit is present in lexicographical publications.